Anti‐GM2 antibodies‐associated meningoradiculitis in the context of HIV immune reconstitution inflammatory syndrome. Issue 2 (31st August 2021) - Forgeard, Nathalie; Januel, Edouard; Blancher, Anne; Fonquernie, Laurent; Gautheret‐Dejean, Agnès; Neil, Jean; Meyohas, Marie‐Caroline
Abstract: Background: Autoimmune manifestations can occur in the context of HIV immune reconstitution inflammatory syndrome (IRIS). Previous studies have shown that GM2 is overexpressed on HIV‐1 infected T lymphocytes. Case presentation: A 71‐year‐old patient diagnosed with HIV‐1 infection developed neurological symptoms congruent with meningoradiculitis 1 month after initiation of antiretroviral therapy. Concurrent syphilitic seroconversion raised the hypothesis of neurosyphilis, which was later infirmed. Serum antiganglioside immunoglobulin M antibodies were highly positive. Treatment with intravenous immunoglobulins was effective. Conclusion: We postulate that meningoradiculitis in this patient was a consequence of anti‐GM2 antibodies produced as part of an anti‐HIV‐1 immune response, and that this case falls within the scope of autoimmune manifestations linked to HIV IRIS. Abstract : Anti‐GM2 antibodies‐associated meningoradiculitis occurred simultaneously with immune restoration in an HIV patient. GM2 is overexpressed on HIV‐infected T lymphocytes, and we showed no cross‐reactivity between GM2 and HIV‐1 glycoproteins in western blot. We believe this case falls within the scope of autoimmune manifestations linked to HIV immune reconstitution inflammatory syndrome.